Efficient exciton to dopant energy transfer in Mn2+-Doped (C4H9NH3)2PbBr4 two-dimensional (2D) layered perovskites - Biswas, A. (Chemistry of Materials, 2017)
Three-dimensional ABX3 perovskite material has attracted immense interest and applications in optoelectronic devices, because of their enabling properties. Recently, Mn2+ doping directly into APbCl3-type three-dimensional (3D) nanocrystals, manifesting host-to-dopant energy transfer, have been reported for LED display applications. Strongly bound excitons in the doped system can enhance the dopant-carrier exchange interactions, leading to efficient energy transfer. Here, we report the simple and scalable synthesis of Mn2+-doped (C4H9NH3)2PbBr4 two-dimensional (2D) layered perovskites. The Mn2+-doped 2D perovskite shows enhanced energy transfer efficiency from the strongly bound excitons of the host material to the d electrons of Mn2+ ions, resulting in intense orange-yellow emission, which is due to spin-forbidden internal transition (4T1 → 6A1) with the highest quantum yield (Mn2+) of 37%. Because of this high quantum yield, stability in ambient atmosphere, and simplicity and scalability of the synthetic procedure, Mn2+-doped 2D perovskites could be beneficial as color-converting phosphor material and as energy down-shift coating for perovskite solar cells. The newly developed Mn2+-doped 2D perovskites can be a suitable material to tune dopant-exciton exchange interactions to further explore their magneto-optoelectronic properties.
Keywords: Doping (additives); Energy Efficiency; Energy Transfer; Exchange interactions; Excitons; Light Emitting Diodes

Surface disordered rutile TiO2-graphene quantum dot hybrids: a new multifunctional material with superior photocatalytic and biofilm eradication properties - Biswas, A.; Salunke, G.; Khandelwal, P.; Das, R.; Poddar, P. (New Journal of Chemistry, 2017)
The controlled introduction of defects in semiconductors has contributed to the development of electronic devices and technologies. Recently, chemical control over defects, formation of new hybrid materials and multifunctional nanostructures have been sought in energy, health, and environment related technologies. Surface-disordered anatase-TiO2 has received wide attention due to its exceptional photocatalytic performance. Herein, we demonstrate, for the first time, a one-step aqueous-phase synthesis of a surface-disordered rutile TiO2-graphene quantum dot (TG) hybrid material. The TG-hybrid is a rutile-TiO2 matrix in which homogeneous in situ insertion of GQDs occurs during the growth of the TiO2 particles. The TG-hybrid material showed superior photocatalytic performance with similar to 98% solar light driven photo-degradation of methylene blue (MB) dye within 6 min and similar to 86% of rhodamine-B (RhB) within 4 min which is much better than the photocatalytic performance shown by the rutile-TiO2 (similar to 30% and similar to 20%, respectively) and GQDs (similar to 15% and similar to 8%, respectively), themselves. Moreover, the TG-hybrid also showed enhanced toxicity to Gram-positive (S. aureus) as well as Gram-negative (E. coli, P. aeruginosa) bacterial cells. The growth-curves of E. coli cells, after incubating them with increasing concentrations of the TG-hybrid, showed that the TG-hybrid could effectively inhibit the growth of E. coli cells at a concentration of 60 mu g mL(-1). The effect of UV-light exposure on the bacterial-biofilm disruption by the TG-hybrid material was also investigated. It was observed that in the presence of UV-light, the biofilm disruption done by the TG-hybrid was larger in comparison to the TiO2 and GQDs alone, under the same conditions. The increase in the formation of reactive oxygen species (ROS) in the presence of sunlight for the TG-hybrid may be the reason behind its superior antibacterial and biofilm eradication properties. We believe that the TG-hybrid material will have applications in energy, health and environment related technologies.